2021
DOI: 10.1038/s41598-021-87175-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphenol A on alterations of ICAM-1 and HLA-G genes expression and DNA methylation profiles in cumulus cells of infertile women with poor response to ovarian stimulation

Abstract: This study aimed to investigate the relationship between follicular fluid Bisphenol A (BPA) concentrations with alterations of ICAM-1 and HLA-G genes and proteins expression as well as methylation profiles in the cumulus cells of poor ovarian response (POR) women based on their healthy lifestyle habit. Eighty women under the age of 35 were divided into two groups: 1—POR without using plastic containers (n = 40) and 2—POR with using plastic containers (n = 40). The ICAM-1 and HLA-G genes and protein expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The researchers also noted that BPA is negatively associated with anti-Müllerian hormone (AMH) and day-3 FSH, but no statistical significance was found [ 27 ]. Two recent studies confirmed the aforementioned data [ 47 , 50 ]. Czubacka et al, in particular, found a negative association of high BPA levels with AFC and AMH [ 47 ].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The researchers also noted that BPA is negatively associated with anti-Müllerian hormone (AMH) and day-3 FSH, but no statistical significance was found [ 27 ]. Two recent studies confirmed the aforementioned data [ 47 , 50 ]. Czubacka et al, in particular, found a negative association of high BPA levels with AFC and AMH [ 47 ].…”
Section: Resultssupporting
confidence: 68%
“…Overall, seven studies have investigated the association between serum or urine BPA concentrations and various IVF outcomes [ 23 , 35 , 41 , 45 , 49 , 50 , 51 ]. Most of them reported the absence of a statistically significant association between high BPA concentrations in various human fluids and IVF outcome measures, namely fertilization, clinical pregnancy, and live birth rates [ 23 , 35 , 41 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human leukocyte antigen-G (HLA-G) plays a role in the maturation of oocytes and embryo implantation. In human CCs, it was found that a low expression of HLA-G was associated with a poor quality of oocytes and poor fertilization and reduced the development of embryos [ 82 ]. Before fertilization, the exposure of COCs to hydrogen peroxide reduced the rates of cleavage, but it did not result in the death of CCs or oocytes.…”
Section: Cumulus Cells With Fertilizationmentioning
confidence: 99%
“…The widespread use of bisphenol A in the food industry is of concern to the scientific community, as this substance can enter the human body. Population studies show that bisphenol A is detected in 95-100% of healthy volunteers [1,2].…”
Section: Introductionmentioning
confidence: 99%